Aplikasi Persediaan Barang Gudang di Ace Hardware Cibinong City Mall Berbasis Android dengan Menggunakan Google Appsheet (Yayasan Kawanad, 2024)
The primary objective of this research is to develop a warehouse inventory application utilizing the Google Appsheet platform, specifically designed for ACE Hardware Cibinong City Mall. The application aims to streamline the recording and monitoring processes of goods entering and exiting the warehouse. This application is designed to provide comprehensive and informative reports on the inventory levels and the distribution of goods. The development approach employed is the Waterfall methodology, which includes stages of requirements analysis, design, implementation, testing, and maintenance. The sample data for the inventory were sourced from the ACE Hardware Cibinong City Mall warehouse to ensure the application meets the specific needs and characteristics of the warehouse. The resulting application features essential functionalities for inputting inventory data and managing the structured recording of goods movements. Additionally, it can generate detailed reports that offer insights into the current status of warehouse inventory. Thus, this application is expected to enhance efficiency and accuracy in warehouse inventory management, providing a valuable solution for ACE Hardware Cibinong City Mall.